Analisis Kinerja Perbankan Ditinjau Dari Aspek Profitabilitas dan Efisiensi (Studi Kasus Pada Bank Yang Terdaftar di Bursa Efek Indonesia Periode 2012- 2014) - Najoan, Holly (JURNAL RISET BISNIS DAN MANAJEMEN, 2016)
The result of this research found that (1) NPL and firm size has not effect on effiency, CAR has a negative effect on efficiency. Risk has a positive effect on efficniency. (2) Corporate Governance, DER and CAR has no effect on profitability. NPL has a negative effect onprofitability, firm size has a positive effect on profitability, and risk has a positive effect on profitability in banking sectorKeywords: Corporate Governance, CAR, NPL, DER, Risk, Firm Size